Implementation of ITE Law in Regulating TikTok Content for Child Protection: Implementasi Undang-Undang ITE dalam Pengaturan Konten TikTok untuk Perlindungan Anak - Sholikhah, Firda Mar’atus; Multazam, Mochammad Tanzil (Indonesian Journal of Law and Economics Review, 2025)
General Background: The rapid growth of digital technology has reshaped communication patterns and media consumption globally. Specific Background: Social media platforms such as TikTok have become highly accessible to minors, often exposing them to inappropriate content due to the absence of effective filtering mechanisms. Knowledge Gap: Limited legal studies have examined the normative enforcement of the Information and Electronic Transactions (ITE) Law concerning child protection in digital spaces. Aims: This study aims to analyze the implementation of the ITE Law in regulating TikTok content lacking special filters for minors and to provide recommendations for strengthening digital protection. Results: Using a normative juridical method with statutory and conceptual approaches, findings show that TikTok’s system does not fully comply with Article 16A Paragraph (4) of Law No. 1 of 2024, which mandates electronic system reliability and safety. Novelty: This study emphasizes the urgency of embedding legal obligations for digital platforms to ensure child safety online. Implications: The research encourages stronger collaboration between regulators, platform providers, and parents to establish a safe digital environment for children. Highlights: TikTok lacks specific filtering for minors as required by law. ITE Law mandates digital system accountability and safety. Strengthened legal cooperation ensures safer online environments for children. Keywords: ITE Law; TikTok; Digital Protection; Child Safety; Legal Regulation